2018
DOI: 10.1042/bsr20180479
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpressed C14orf166 associates with disease progression and poor prognosis in non-small-cell lung cancer

Abstract: Chromosome 14 ORF 166 (C14orf166), a protein involved in the regulation of RNA transcription and translation, has been reported to possess the potency to promote tumorigenesis; however, the role of C14orf166 in non-small-cell lung cancer (NSCLC) remains unknown. The purpose of the present study was to assess C14orf166 expression and its clinical significance in NSCLC. Immunohistochemical staining, quantitative real-time PCR (qRT-PCR), and Western blotting were used to detect the C14orf166 protein and mRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…It has been suggested that the overexpression of C14orf166 has a role in the development of nonsmall-cell lung cancer, and it would be beneficial to consider it in the treatment of high-risk patients. 33 It has been reported that this protein is overexpressed in breast cancer. 34 The expression of both the C14orf166 mRNA and protein was also found to be upregulated in cervical cancer cell lines and tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the overexpression of C14orf166 has a role in the development of nonsmall-cell lung cancer, and it would be beneficial to consider it in the treatment of high-risk patients. 33 It has been reported that this protein is overexpressed in breast cancer. 34 The expression of both the C14orf166 mRNA and protein was also found to be upregulated in cervical cancer cell lines and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The C14orf166, a multifunctional protein with these properties, is associated with some cancer types. It has been suggested that the overexpression of C14orf166 has a role in the development of nonsmall‐cell lung cancer, and it would be beneficial to consider it in the treatment of high‐risk patients 33 . It has been reported that this protein is overexpressed in breast cancer 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The C14orf166, a multifunctional protein with these properties, is associated with some cancer types. It has been suggested that the overexpression of C14orf166 has a role in the development of non-small-cell lung cancer (NSCLC), and it would be beneficial to consider it in the treatment of high-risk patients 32 . It has been reported that this protein is overexpressed in breast cancer 33 .…”
Section: Discussionmentioning
confidence: 99%
“…PRDX1 could modulate cellular apoptosis via scavenging intracellular reactive oxygen species in AGS cells [44,45]. IRF2BP2 and C14orf166 have been reported to possess the potency to promote tumorigenesis [46,47]. IRF2BP2 as a transcriptional repressor overexpresses in gastric cancer cells, which is closely related to proliferation, migration, and invasion in gastric cancer [48].…”
Section: Biomed Research Internationalmentioning
confidence: 99%